Design of experiment approach to leukemia studies - Tan, Jeremy Zhi Qiang. (2011)
Cancer remains a leading cause of death worldwide, accounting for 7.9 million deaths in 2007, and is projected to rise to an estimated 12 million deaths in year 2030. To date, an extensive amount of work has been done to characterize the therapeutic effects and toxicity of anti-cancer compounds as well as the effects of cytokines on the expansion of HSC. However, conventional approaches often employ a dose-response method which neglects to consider interactive effects. In addition, there is a lack of use of a statistically optimized experimental design in current biological practices and cell culture studies.